PERAN ORANG TUA DAN PENDIDIK DALAM PENDAMPINGAN ANAK DI ERA GEDGET - Heri Rusli Effendi; Siminto Siminto; Muslimah Muslimah (Jurnal Bintang Pendidikan Indonesia, 2023)
Education is the basic thing that is needed by humans to face the challenges of life, education also plays a very important role in determining the future of future generations. The educational process, both the means and methods, always evolves to keep up with the times, so educators or designers of educational methods must always update to adapt to the challenges of the times. So that we are not left behind by the progress of the times and advances in information technology. Currently we are in the millennial era of Generation X or what we are more familiar with calling it the Now Age, so it is imperative that all educational patterns, methods and educational facilities adapt to the Minenia Era or the Now Age Generation. Advances in technology in the field of information and communication is a useful thing in the world of science. Likewise with our children, they live not in our time, they live with the challenges of technological progress and information that is so fast, our children should always be able to keep up with the times and take advantage of technological advances to make it easier for them to carry out the learning process and obtain various information. useful for life. So the authors think it is very important for children to always interact with current information technology developments.